2022
DOI: 10.1097/iae.0000000000003538
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Optical Coherence Tomography Angiography in Patients With Preeclampsia

Abstract: We investigated microvascular changes in the retina and optic disk by comparing the optical coherence tomography angiography findings in preeclamptic patients with those in control groups and also evaluated the preeclamptic patients after delivery. Optical coherence tomography angiography diagnosed decreased deep capillary plexus vessel density values in patients with preeclampsia, but these results improved after delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Our study is the first to present long‐term VD indices after HDP, including VSD and VDI. Two other studies have investigated VD in preeclamptic women during pregnancy ( n = 150 and n = 98; Ciloglu et al., 2019; Özcan et al., 2022). Similar to our postpartum findings, the authors found no differences in VD during pregnancy in the superficial parafoveal area (which was equivalent to the investigated area in our study).…”
Section: Discussionmentioning
confidence: 99%
“…Our study is the first to present long‐term VD indices after HDP, including VSD and VDI. Two other studies have investigated VD in preeclamptic women during pregnancy ( n = 150 and n = 98; Ciloglu et al., 2019; Özcan et al., 2022). Similar to our postpartum findings, the authors found no differences in VD during pregnancy in the superficial parafoveal area (which was equivalent to the investigated area in our study).…”
Section: Discussionmentioning
confidence: 99%
“…Pertaining to preeclampsia, similar findings to those detected in hypertension have been observed. Both the superficial and deep foveal & parafoveal densities were recorded to be significantly lower in preeclamptic women compared to healthy pregnant & non-pregnant individuals [ 32 , 33 ]. Hata et al [ 34 ] documented diminished pulsatility in the ophthalmic artery in preeclamptic patients compared to healthy pregnant women using Doppler imaging.…”
Section: Discussionmentioning
confidence: 99%